Die werk van die 'American board of Commissioners for Foreign Missions' (A.B.C.F.M.) in Suid-Afrika 1835-1945 - Kellerman, P. S.(Paulus Stefanus) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (B. Ed.) -- Universiteit van Stellenbosch, 1946.